2007
DOI: 10.1186/1744-8069-3-39
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Pharmacology of Trichloro(Sulfanyl)ethyl Benzamides as Transient Receptor Potential Ankyrin 1 (TRPA1) Antagonists

Abstract: Agonists of TRPA1 such as mustard oil and its key component AITC cause pain and neurogenic inflammation in humans and pain behavior in rodents. TRPA1 is activated by numerous reactive compounds making it a sensor for reactive compounds in the body. Failure of AITC, formalin and other reactive compounds to trigger pain behavior in TRPA1 knockout mice, as well as the ability of TRPA1 antisense to alleviate cold hyperalgesia after spinal nerve ligation, suggest that TRPA1 is a potential target for novel analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 31 publications
3
80
0
Order By: Relevance
“…In addition to reactive chemical activators, cold temperature has been shown to activate TRPA1 in recombinant expression systems (Story et al, 2003;Corey et al, 2004;Story and Gereau, 2006;Klionsky et al, 2007). Furthermore, recent studies unequivocally showed that cold indeed activates TRPA1 in calcium imaging experiments as well as in single channel recordings (Sawada et al, 2007).…”
Section: Camentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to reactive chemical activators, cold temperature has been shown to activate TRPA1 in recombinant expression systems (Story et al, 2003;Corey et al, 2004;Story and Gereau, 2006;Klionsky et al, 2007). Furthermore, recent studies unequivocally showed that cold indeed activates TRPA1 in calcium imaging experiments as well as in single channel recordings (Sawada et al, 2007).…”
Section: Camentioning
confidence: 99%
“…Generation of Chinese hamster ovary (CHO) cell lines stably expressing human transient receptor potential ankyrin 1 (hTRPA1), rat transient receptor potential ankyrin 1 (rTRPA1), or human transient receptor potential melastatin 8 (hTRPM8) and their functional characterizations were previously described (Klionsky et al, 2007;Gavva et al, 2012). To construct the hTRPA1-FLAG sequence, a DNA fragment encoding the FLAG tag (DYKDDDDK) was inserted into the predicted extracellular loop 1 of hTRPA1 at amino acid 756.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AMG5445 inhibits human TRPA1, but activates rat TRPA1 [ 70 ]. The pharmacological profi le of the human and rhesus monkey TRPA1 is relatively distinct from mouse and rat TRPA1 [ 94 ].…”
Section: Modulation Of Trpa1 By Other Activators and Inhibitorsmentioning
confidence: 99%